Effect of Perceived Ease of Use on Intention to Reuse Flip via Perceived Usefulness in Islamic Business - Lusiana, Mia; Siska Yuli , Anita; Rahman, Taufiqur (Research Horizon, 2025)
This study aims to evaluate the effect of Perceived Ease of Use on Behavioral Intention to Reuse the Flip application, with Perceived Usefulness as an intervening variable. This study involved 96 respondents from an unknown population. Data collection was carried out by distributing questionnaires using a Likert scale. Data analysis was carried out using the Partial Least Square Structural Equation Modeling (PLS-SEM) method using SmartPLS 4 software. The analysis process includes validity, reliability, hypothesis testing, and model fit testing. The results showed that Perceived Ease of Use has a positive and significant effect on Behavioral Intention to Reuse the Flip application. In addition, Perceived Ease of Use also has a significant effect on Perceived Usefulness. However, the results showed that Perceived Usefulness did not have a significant effect on Behavioral Intention to Reuse the Flip application. Therefore, Perceived Usefulness was not proven to mediate the relationship between Perceived Ease of Use and Behavioral Intention. This finding suggests that ease of use of the application has a greater effect on reuse intentions than perceptions of its usefulness.